Riti di passaggio: una lettura girardiana (Itinera, 2012)
Through the analisys of Rene Girard’s works, which develops Arnold Van Gennep’s thesis, it’s possible to provide a specific meaning to one of the most controversial phenomena of antropology, i.e. the violence which features the initiation rituals in the archaic societies. Following this we are led to the interpretation of some contemporary social issues and, with reference to the archaic initiation scheme, to the demonstration of how these are still present and predominant in our current social life.